Achieving High Coverage of H1N1 Influenza Vaccine in an Ethnically Diverse Obstetric Population: Success of a Multifaceted Approach - Kara K. Hoppe; Linda O. Eckert (Hindawi Limited, 2011)
Objective. To report on a multifaceted approach to increase uptake of the H1N1 vaccine in our ethnically diverse obstetrical population. Methods. A review of our obstetric clinic vaccine registry and the approaches used to increase vaccine uptake. We created a real-time vaccine registry, educated patients in their own language via educational videos and use of cultural case workers, facilitated patient appointments and transportation, educated staff, and used other interventions to enhance immunization uptake. Results. Within the first month of H1N1 availability, we vaccinated 120 of our total 157 obstetrics patients. Our overall coverage rate was 76% (number vaccinated/total number eligible.) Of the enrolled patients, the vaccine acceptance rates were similar in our English (59 (78%) of 76) versus non-English (59 (75%) of 79) speaking patients. Conclusions. High vaccine coverage is possible in an ethnically diverse, highly immigrant obstetrics population.